Burn-Induced Coagulopathies: a Comprehensive Review. Issue 2 (August 2020) - Ball, Robert L.; Keyloun, John W.; Brummel-Ziedins, Kathleen; Orfeo, Thomas; Palmieri, Tina L.; Johnson, Laura S.; Moffatt, Lauren T.; Pusateri, Anthony E.; Shupp, Jeffrey W.
Abstract : ABSTRACT: Burn-induced coagulopathy is not well understood, and consensus on diagnosis, prevention, and treatments are lacking. In this review, literature on burn-induced (and associated) coagulopathy is presented along with the current understanding of the effects of burn injury on the interactions among coagulation, fibrinolysis, and inflammation in the acute resuscitative phase and reconstructive phase of care. The role of conventional tests of coagulopathy and functional assays like thromboelastography or thromboelastometry will also be discussed. Finally, reported methods for the prevention and treatment of complications related to burn-induced coagulopathy will be reviewed.